Antisense imaging of epidermal growth factor-induced p21(WAF-1/CIP-1) gene expression in MDA-MB-468 human breast cancer xenografts. - Wang, J; Chen, P; Mrkobrada, M; Hu, M; Vallis, K; Reilly, R (2003)
Molecular imaging of the expression of key genes which determine the response to DNA damage following cancer treatment may predict the effectiveness of a particular treatment strategy. A prominent early response gene for DNA damage is the gene encoding p21(WAF-1/CIP-1), a cyclin-dependent kinase inhibitor that regulates progression through the cell cycle. In this study, we explored the feasibility of imaging p21(WAF-1/CIP-1) gene expression at the mRNA level using an 18-mer phosphorothioated antisense oligodeoxynucleotide (ODN) labeled with (111)In. The known induction of the p21(WAF-1/CIP-1) gene in MDA-MB-468 human breast cancer cells following exposure to epidermal growth factor (EGF) was used as an experimental tool. Treatment of MDA-MB-468 cells in vitro with EGF (20 n M) increased the ratio of p21(WAF-1/CIP-1) mRNA/beta-actin mRNA threefold within 2 h as measured by the reverse transcription polymerase chain reaction (RT-PCR). A concentration-dependent inhibition of EGF-induced p21(WAF-1/CIP-1) protein expression was achieved in MDA-MB-468 cells by treatment with antisense ODNs with up to a tenfold decrease observed at 1 microM. There was a fourfold lower inhibition of p21(WAF-1/CIP-1) protein expression by control sense or random sequence ODNs. Intratumoral injections of EGF (15 microg/dayx3 days) were employed to induce p21(WAF-1/CIP-1) gene expression in MDA-MB-468 xenografts implanted subcutaneously into athymic mice. RT-PCR of explanted tumors showed a threefold increased level of p21(WAF-1/CIP-1) mRNA compared with normal saline-treated tumors. Successful imaging of EGF-induced p21(WAF-1/CIP-1) gene expression in MDA-MB-468 xenografts was achieved at 48 h post injection of (111)In-labeled antisense ODNs (3.7 MBq; 2 microg). Tumors displaying basal levels of p21(WAF-1/CIP-1) gene expression in the absence of EGF treatment could not be visualized. Biodistribution studies showed a significantly higher tumor accumulation of (111)In-labeled antisense ODNs in the presence of EGF induction of the p21(WAF-1/CIP-1) gene (0.32%+/-0.06% injected dose/g) compared with normal saline-treated control mice (0.11%+/-0.07% injected dose/g). The tumor/blood ratio for antisense ODNs in the presence of EGF induction of the p21(WAF-1/CIP-1) gene (4.87+/-0.87) was also significantly higher than for control random sequence ODNs (2.14+/-0.69) or for mice receiving antisense ODNs but not treated with EGF (2.07+/-0.37). We conclude that antisense imaging of upregulated p21(WAF-1/CIP-1) gene expression is feasible and could represent a promising new molecular imaging strategy for monitoring tumor response in cancer patients. To our knowledge, this study also describes the first report of molecular imaging of the upregulated expression of a downstream gene target of the EGFR, a transmembrane tyrosine kinase receptor.